2019
DOI: 10.1088/1758-5090/ab15cf
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted biofabrication and bioprinting of preferentially aligned three-dimensional cellular constructs

Abstract: A critical consideration in tissue engineering is to recapitulate the microstructural organization of native tissues that is essential to their function. Scaffold-based techniques have focused on achieving this via the contact guidance principle wherein topographical cues offered by scaffold fibers direct migration and orientation of cells to govern subsequent cell-secreted extracellular matrix organization. Alternatively, approaches based on acoustophoretic, electrophoretic, photophoretic, magnetophoretic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 70 publications
0
61
0
Order By: Relevance
“…3e) indicated that the experimentally measured T construct after 30 min (38.9 °C) was close to the computational model estimate (37 °C). The slightly higher experimental T construct could be attributed to fluid streaming-induced perturbations observed for the 1.5 MHz transducers 40 , which may have caused a mixing of the high temperature fluid near the transducer with the low temperature fluid in the construct region.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…3e) indicated that the experimentally measured T construct after 30 min (38.9 °C) was close to the computational model estimate (37 °C). The slightly higher experimental T construct could be attributed to fluid streaming-induced perturbations observed for the 1.5 MHz transducers 40 , which may have caused a mixing of the high temperature fluid near the transducer with the low temperature fluid in the construct region.…”
Section: Resultsmentioning
confidence: 96%
“…This could be attributed to the viscous streams at the initiation of each excitation burst, wherein the PBS is scattered away from the transducer every 1 s. For each construct, the top layer exhibits a greater degree of 3D alignment, while the bottom layer exhibits a greater degree of alignment near the top. This could be attributed to a greater compliance of the transducer surface near its top region as compared to its bottom 40 . This non-uniform compliance could also explain the increased tilting of cellular arrays in the top layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a different application, but still relevant to bioprinting, computational force modeling of the tip movement inside gels with different viscoelastic properties was used to design and create channels within the material (Barua et al, 2020). Similarly, a combination of physical modeling of acoustic waves and engineering solutions was used to pattern cells within a bioprinted cartilage precursor via ultrasound (Chansoria et al, 2019).…”
Section: Bioprinting and Mechanical Modelingmentioning
confidence: 99%